Enabling user-inclusive innovation in African Agriculture - Brännvall, Ruth (Technical Centre for Agricultural and Rural Cooperation, 2016)
Ignitia has developed a disruptive technology that allows smallholder farmers in West Africa to access accurate weather predictions. Engaging with local partners and initiating reliable impact measurements were key factors to gain trust and scale-up the business.